Detection and analysis of nanoparticles in patients: A critical review of the status quo of clinical nanotoxicology. (January 2016) - Bitounis, Dimitrios; Pourchez, Jérémie; Forest, Valérie; Boudard, Delphine; Cottier, Michèle; Klein, Jean-Philippe
Abstract: On the cusp of massive commercialization of nanotechnology-enhanced products and services, the physical and chemical analysis of nanoparticles in human specimens merits immediate attention from the research community as a prerequisite for a confident clinical interpretation of their occurrence in the human organism. In this review, we describe the caveats in current practices of extracting and isolating nanoparticles from clinical samples and show that they do not help truly define the clinical significance of detected exogenous nano-sized objects. Finally, we suggest a systematic way of tackling these demanding scientific tasks. More specifically, a precise and true qualitative evaluation of nanoparticles in human biological samples is still hindered by various technical reasons. Such a procedure is more refined when the nature of the pollutants is known, like in the case of nano-sized wear debris originating from biomedical prostheses. Nevertheless, nearly all available analytical methods provide unknown quantitative accuracy and qualitative precision due to the challenging physical and chemical nature of nanoparticles. Without trustworthy information to describe the nanoparticulate load of clinical samples, it is impossible to accurately assess its pathological impact on isolated cases or allow for relevant epidemiological surveys on large populations. Therefore, we suggest that the many and various specimens stored in hospitals be used for the refinement of methods of exhaustive quantitative and qualitative characterization of prominent nanoparticles in complex human milieu.